MOTHER'S ATTITUDE AND HUSBAND SUPPORT TOWARD NEWBORN BABY VISIT AT RAWASARI COMMUNITY HEALTH CENTER, JAMBI - Adelina Fitri; Delta Intan Putri; Andy Amir; Hubaybah Hubaybah; Fitria Eka Putri; Ashar Nuzulul Putra (POLTEKKES KEMENKES JAYAPURA, 2022)
One of the efforts that can be made to prevent abnormalities in newborns that can affect life-long disability and even death was to increase neonatal visits. This study aimed to determine the factors associated with neonatal visits on the factors of age, education, occupation, attitudes, knowledge, distance to health care, and husband's support in the work area of Rawasari Primary Health Care, Jambi City in 2020. The study design was cross-sectional, the population in this study were mothers who had babies aged 1-3 months at the Rawasari Primary Health Care. The sample amounted to 91 people. The sampling technique used simple random sampling. Data collection was done from March-June 2020. Data analysis used univariate and bivariate chi-square. The results of this study showed that 63% of respondents did not make regular neonatal visits. Age (PR = 0.91; 95% CI = 0.66-1.24) education (PR = 1.30; 95% CI = 0.94-1.75) occupation (PR = 1.11; 95% CI = 0.82-1.51) attitude (PR = 1.43; 95% CI = 1.05-1.93) knowledge (PR = 1.41 95% CI = 0.90-2.20 ) husband's support (PR = 1.95; 95% CI = (1.14-3.33) and distance to health care (PR = 0.92: 95% CI = 0.62-1.37). husband's support had the highest risk of not having regular neonatal visits. There was a significant relationship between a neonatal visit with attitude and the husband's support in Rawasari Primary Health Care Jambi city. The husband's support in accompanying mothers to health services should be improved because the highest risk in irregular neonatal visits. Keywords: Maternal attitudes, Neonatal assessment, Spouse support